Disequilibrium and the Marginal Productivity of Capital and Labor - Thurow, Lester C. (The Review of Economics and Statistics, 1968)
D IFFERENTIATING a production function with respect to capital and labor yields equations for the marginal productivity of capital and the marginal productivity of labor. The variables that determine the marginal products in these equations are the same as those in the production function. If the data used to estimate the parameters of the production function are inserted into the equations for the marginal products, the marginal productivities of both capital and labor can be estimated empirically. The same data and equations also make it possible to determine the causes of any changes in the marginal products. How much of the rising marginal productivity of labor is caused by technical progress; how much is caused by a rising capital-labor ratio? If the economy is in equilibrium and there are no economies or diseconomies of scale, actual and marginal returns should be identical. Any differences between the estimated marginal products and the actual returns to capital and labor means that the economy is in disequilibrium; the size of the differences measures the extent of disequilibrium. If disequilibrium does exist, what causes the observed pattern? What are its implications for investment decisions in both human and physical capital? This paper applies the above approach to the American economy from 1929 to 1965.